Librarian's guide to online searching : cultivating database skills for research and instruction - Brown, Christopher C., 1953-; Bell, Suzanne S. (Santa Barbara Libraries Unlimited, 2018)
"This book describes the background of how databases work; how they are constructed and in the case of some databases; how they transitioned from the legacy print world to an online environment; how technologies within databases can interact with other products like bibliography citation services, outbound linking to full text content, and social media mentions; and the methods used by libraries to provide access to licensed content from anywhere in the world"--
Introduction to library databases -- How databases work -- Controlled vocabularies -- The searcher's toolkit: part 1 -- The searcher's toolkit: part 2 -- Database interfaces: vendor features and variations -- Social science databases -- Government information databases -- Humanities databases -- Science, engineering, and medical databases -- Numerical and statistical databases -- From bibliographic databases to full text ebooks -- Web-scale discovery databases -- User behaviors and meeting information needs -- Evaluating databases -- Teaching other people about databases.
The first named author of the 4th edition (2015) was Suzanne S. Bell.
Includes bibliographical references and index.
Keywords: Database searching; Electronic information resource searching